2005
DOI: 10.1124/jpet.105.084905
|View full text |Cite
|
Sign up to set email alerts
|

A Farnesoid X Receptor-Small Heterodimer Partner Regulatory Cascade Modulates Tissue Metalloproteinase Inhibitor-1 and Matrix Metalloprotease Expression in Hepatic Stellate Cells and Promotes Resolution of Liver Fibrosis

Abstract: The farnesoid X receptor (FXR) is expressed by and regulates hepatic stellate cells (HSCs). In the present study, we investigated whether 6-ethyl chenodeoxycholic acid (6-ECDCA or INT-747), a semisynthetic derivative of chenodeoxycholic acid (CDCA), modulates tissue metalloproteinase inhibitor (TIMP)-1 and matrix metalloprotease (MMP)-2 expression/activity in HSCs and in the liver of rats rendered cirrhotic by 4-week administration of CCl 4 . Exposure of HSCs to FXR ligands increases small heterodimer partner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 39 publications
4
105
0
Order By: Relevance
“…29) It has been suggested that TIMP-1 plays an important role in the pathogenesis of liver fibrosis. 31) Consistenly with previously published work, we observed elevated levels TIMP-1 and decreased expression of MMP-13 upon treatment with CCl 4 . 24,32) The resulting disruption of the balance between TIMP-1 and MMP-13 promotes the accumulation of fibrillar collagens and leads to the development of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 72%
“…29) It has been suggested that TIMP-1 plays an important role in the pathogenesis of liver fibrosis. 31) Consistenly with previously published work, we observed elevated levels TIMP-1 and decreased expression of MMP-13 upon treatment with CCl 4 . 24,32) The resulting disruption of the balance between TIMP-1 and MMP-13 promotes the accumulation of fibrillar collagens and leads to the development of hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 72%
“…In additional models of liver cirrhosis and fibrosis, treatment with the FXR agonist 6-ethyl chenodeoxycholic acid causes decreased expression of 1) TGF-␤1, 2) tissue metalloproteinase inhibitor-1 and -2, 3) ␣1 (I) collagen, 4) ␣ smooth muscle actin, and 5) increased expression and activity of matrix metalloproteinase-2. These effects result in resolution of hepatic fibrosis (38). Our results therefore also indicate that the decrease in FXR and its major target (SHP) could also mediate the increased expression of TGF-␤ in the kidney, resulting in podocyte loss, accumulation of extracellular matrix proteins, renal fibrosis, and proteinuria.…”
Section: Discussionmentioning
confidence: 65%
“…SHP is also a known target for other nuclear receptors, including the estrogen receptors and PPAR␥ (65,66), and is essential in the regulation of the expression/activity of hepatocyte NF4 and retinoid X receptor (66). A body of evidence suggest that SHP represents an important mediator of FXR activity and acts as a corepressor of FXR target genes in different physiological contexts (33,36,46,47). To investigate the molecular mechanism(s) by which FXR regulates OPN production, we conducted in vitro experiments using a NKT cell hybridoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SHP mediates some of the regulatory activities exerted by FXR (33,36,46,47). SHP is an atypical nuclear receptor, lacking a ligand-binding domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation